Improving Students’ English Language Skills through Digital Gamification-based Learning : An Action Research Study - Losi, Rizky Vita; Panggabean, Hanna Maria; Harahap, Ahmad Fadli; Hamdanur, Roobby; Tanjung, Rovidatul Hikmah (Indonesian Research Journal on Education, 2025)
This study investigates the effectiveness of gamification-based applications in improving students' English language skills, including speaking, listening, reading, and writing. The Cake application, used for speaking and listening skills, and the Wordwall application, used for reading and writing skills, were implemented to enhance student proficiency. Pre-test and post-test analyses revealed significant improvements across all skills. The average speaking skill score increased by 15.5 points, indicating a notable enhancement in students' confidence and fluency. In listening skill, students' post-test score averaged 85.75, a significant increase from 61.5 in the pre-test, showing that gamification effectively boosts listening comprehension. For reading skill, the Wordwall app led to an average post-test score of 85.8, up from 61.1, demonstrating gamification’s role in increasing student motivation and reading comprehension. Similarly, in writing skill, students showed an average post-test score of 86.4, a substantial rise from 60.3 in the pre-test, highlighting the positive impact of interactive writing tasks. The findings support the research of Cheng et al. (2025), Rodríguez et al. (2023), Matyakhan et al. (2024), and Ibrahim et al. (2024), confirming that gamification enhances student engagement, motivation, and academic performance. This study provides strong evidence that gamification-based learning is highly effective in improving English language skills at the vocational level, suggesting that its implementation in higher education can significantly support students' language development and prepare them for professional careers.